Homocysteinylated alpha 1 antitrypsin as an antigenic target of autoantibodies in seronegative rheumatoid arthritis patients. Issue 113 (September 2020) - Colasanti, Tania; Sabatinelli, Danilo; Mancone, Carmine; Giorgi, Alessandra; Pecani, Arbi; Spinelli, Francesca Romana; Di Giamberardino, Alessandra; Navarini, Luca; Speziali, Mariangela; Vomero, Marta; Barbati, Cristiana; Perricone, Carlo; et al.
Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease and rheumatoid factor (RF) and anti-citrullinated protein antibodies (ACPA) are the most frequently detected autoantibodies (autoAbs). To date, more than 20% of RA cases are still defined as seronegative forms (seronegative RA, SN-RA). The aim of this study was to identify new antigenic targets of autoAbs in RA patients, which can also be recognized in SN-RA. Using a proteomic approach, we tested sera from SN-RA patients by analyzing synovial fluid (SF) proteins from these patients. Sera from SN-RA patients revealed a strong reactive spot, corresponding to alpha 1 antitrypsin (A1AT). Reverse-phase nanoliquid chromatography and tandem mass spectrometry (Matrix Assisted Laser Desorption/Ionization-Time Of Flight, MALDI-TOF/TOF) confirmed the presence of A1AT in SF and showed that homocysteinylation was one of the post-translational modifications of A1AT. Homocysteinylated (Hcy)-A1AT immunoprecipitated from SN-RA patients' SFs and in vitro modified Hcy-A1AT were used as antigens by Enzyme-Linked ImmunoSorbent Assay (ELISA) to test the presence of specific autoAbs in sera from 111 SN-RA patients, 132 seropositive (SP)-RA patients, and from 95 patients with psoriatic arthritis, 40 patients with osteoarthritis, and 41 healthy subjects as control populations. We observed that a large portion of SN-RA patients (75.7%), and also most of SP-RA patients' sera (87.1%) displayed anti-Hcy-A1AT autoAbs (anti-HATA). Native A1AT was targeted at a lower rate by SP-RA patients autoAbs, while virtually no SN-RA patients' sera showed the presence of anti-native A1AT autoAbs. In conclusion, anti-HATA can be considered potential biomarkers for RA, also in the SN forms. The discovery of novel autoAbs targeting specific autoantigens can represent higher clinic significance for all RA patients' population. Graphical abstract: Image 1 Highlights: RF and ACPA in patients' sera are biomarkers used for the diagnosis of RA. More than 20% of RA cases are still defined as seronegative forms (SN-RA). By a proteomic approach, homocysteinylated (Hcy)-A1AT was detected in the synovial fluid of SN-RA patients. ELISA showed specific autoAbs towards Hcy-A1AT in SN-RA patients' sera.